2001
DOI: 10.1021/es001399u
|View full text |Cite
|
Sign up to set email alerts
|

Regional Characteristics of Sulfur and Lead Isotope Ratios in the Atmosphere at Several Chinese Urban Sites

Abstract: Sulfur and lead isotope ratios in the atmosphere were measured at several selected sites (Harbin, Changchun, Dalian, Waliguan, Shanghai, Nanjing, Guiyang) in China and Tsukuba (Japan), to reveal regional sources characteristics over Eastern Asia. Average S isotope ratios for SO2 and sulfate in the atmosphere in China were close to those of the coals used in each region, indicating a considerable contribution of coal combustion to the sulfur compounds in the atmosphere. Most northern cities had around 5% sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
190
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(212 citation statements)
references
References 48 publications
18
190
2
2
Order By: Relevance
“…Thus, we concluded that the SO x produced by the combustion of local coal was the main source of anthropogenic sulfate in the rainwaters. This is same as was found in other studies of rain in China (Aas et al, 2007;Larssen et al, 2006;Mukai et al, 2001;Xiao and Liu, 2002). The δ 34 S-SO 4 2-NSS of precipitation of type SE, type SW, and type S were -10.7‰, -9.2‰, and -8.0‰, respectively, and we link these differences to different sulfate sources, as these samples were collected in the same season, between the end of May and the beginning of June, 2007.…”
Section: Enrichment Factors and Source Contributions Elementsupporting
confidence: 87%
“…Thus, we concluded that the SO x produced by the combustion of local coal was the main source of anthropogenic sulfate in the rainwaters. This is same as was found in other studies of rain in China (Aas et al, 2007;Larssen et al, 2006;Mukai et al, 2001;Xiao and Liu, 2002). The δ 34 S-SO 4 2-NSS of precipitation of type SE, type SW, and type S were -10.7‰, -9.2‰, and -8.0‰, respectively, and we link these differences to different sulfate sources, as these samples were collected in the same season, between the end of May and the beginning of June, 2007.…”
Section: Enrichment Factors and Source Contributions Elementsupporting
confidence: 87%
“…Sulfur from coal combustion is an important source for atmospheric sulfur in China (Mukai et al, 2001;Guo et al, 2010). It is reported that the d 34 S values of atmospheric sulfate in different regions of China are associated with local coal combustion (Mukai et al, 2001).…”
Section: Sulfur and Oxygen Isotopes In Sulfatementioning
confidence: 99%
“…Guo et al, 2016). Many investigations have been conducted in Europe (Sinha et al, 2008), China (Mukai et al, 2001;Guo et al, 2010;, Japan (Sakata et al, 2013) and Antarctica (Kunasek et al, 2010) to trace atmospheric sulfate sources using sulfur isotopes. Recently, Z. investigated the sulfur isotopic composition of PM 2.5 in Nanjing and identified the major sulfur sources of PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (e.g., Mukai et al 2001;Xiao and Liu 2002;Zhang et al 2010a) have suggested that coal burning gives a significant contribution to rainwater sulfate in most Chinese cities. The δ 34 S values of Chinese coals exhibit a very wide range (−15 to + 50‰).…”
Section: Sulfur Isotope Composition Of Sulfate In Precipitationsmentioning
confidence: 95%